1993
DOI: 10.2165/00003088-199325010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Optimisation of General Anaesthesia in Pregnancy

Abstract: A significant proportion of women require general anaesthesia during pregnancy or for delivery. There are many practical difficulties in studying anaesthetic drugs and techniques to determine what may be best for both the mother and fetus. Physiological changes of pregnancy may alter the pharmacokinetics and pharmacodynamics of anaesthetics and the fetal disposition of drugs is largely unknown. With the limited pharmacokinetic data available, conclusions on the suitability of drugs are reached in conjunction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 95 publications
0
11
0
1
Order By: Relevance
“…Numerous factors determine final concentrations of anesthetics in the fetus following maternal administration. Differences in the adsorption, distribution, and metabolism of the particular anesthetic in the mother, physicochemical and structural characteristics of the specific drug in relation to placental transfer (e.g., lipid solubility, molecular weight and structure, type of transport, protein binding), as well as the physiologic characteristics of the maternal-placental-fetal unit (placental structure, function, membrane thickness, maternal-fetal pH gradients) determine the rate and extent of drug transfer across the placenta (Benitz & Druzin, 2005;Gin, 1993;Nau & Plonait, 1998;Wright & Catz, 1998). Different anesthetic compounds exert unique neuropharmacological actions and clinical effects (Goodman & Gilman, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous factors determine final concentrations of anesthetics in the fetus following maternal administration. Differences in the adsorption, distribution, and metabolism of the particular anesthetic in the mother, physicochemical and structural characteristics of the specific drug in relation to placental transfer (e.g., lipid solubility, molecular weight and structure, type of transport, protein binding), as well as the physiologic characteristics of the maternal-placental-fetal unit (placental structure, function, membrane thickness, maternal-fetal pH gradients) determine the rate and extent of drug transfer across the placenta (Benitz & Druzin, 2005;Gin, 1993;Nau & Plonait, 1998;Wright & Catz, 1998). Different anesthetic compounds exert unique neuropharmacological actions and clinical effects (Goodman & Gilman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ether, however, is characterized by high blood solubility that can be associated with accumulation in the fetal blood and tissues, and altered neurobehavioral function (Hodgkinson, Marx, Kim, & Miclat, 1977;Palahniuk, Scatliff, Biehl, Wiebe, & Sankaran, 1977). In contrast, isoflurane (1-chloro-2,2, 2-trifluoroethyl difluoromethyl ether), is a halogenated compound with low blood solubility (Gin, 1993) that is often used in the delivery room and is not associated with fetal depression or reduced Apgar scores in the newborn (Mattingly, D'Alessio, & Ramaathan, 2003;Ostheimer, 1984). In the present study, we tested the hypothesis that chemomyelotomy of late pregnant rats under ether, as compared to isoflurane, inhalant anesthesia is associated with greater behavioral depression of fetuses that may persist into postnatal life.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the use of anaesthesia during pregnancy concluded that a normal foetus is able to withstand a variety of modern anaesthetic techniques and no currently used anaesthetics are known to be teratogenic. However, drugs like propofol, suxamethonium, isoflurane and nitrous oxide, which are rapidly eliminated by the mother and the neonate, should be used to minimise the exposure [10]. Other concern in such cases would be an increased risk of irradiation to the foetus.…”
Section: Discussionmentioning
confidence: 99%
“…The most critical time regarding teratogenesis following chemical exposure in humans is thought to be during organogenesis which occurs between 15 and 65 days of gestation. 6 Few antibiotics can be used with relative safety during pregnancy under the principle of Food and Drug Administration's Pregnancy Category. 1 Nitrous oxide and isoflurane are the current general anesthetic agents for use during pregnancy with the most favourable pharmacokinetic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…1 Nitrous oxide and isoflurane are the current general anesthetic agents for use during pregnancy with the most favourable pharmacokinetic profiles. 6 Data regarding radiation-induced cancer after exposure to one milligray during the second or third trimester suggest that the risk of fatalites in children younger than 14 years of age may be on the order of 1 in 15,000 children. 7 By way of comparison, the risk ratio for a 50-milligray exposure is about 1:300.…”
Section: Discussionmentioning
confidence: 99%